2011
DOI: 10.2147/vhrm.s21753
|View full text |Cite
|
Sign up to set email alerts
|

Combined determination of highly sensitive troponin T and copeptin for early exclusion of acute myocardial infarction: first experience in an emergency department of a general hospital

Abstract: Background:The purpose of this observational study was to test the diagnostic performance of the Elecsys® troponin T high-sensitive system combined with copeptin measurement for early exclusion of acute myocardial infarction (MI) in clinical practice.Methods:Troponin T high-sensitive (diagnostic cutoff: <14 pg/mL) and copeptin (diagnostic cutoff: <14 pmol/L) levels were determined at admission in addition to other routine laboratory parameters in patients with suspected acute MI presenting to the emergency dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…The temporal release pattern of copeptin in our study was characterized by increased values very early after symptom onset, a peak in ambulance or at admission, and a rapid decrease within the first hours after admission. Copeptin concentrations returned to baseline in all diagnoses after 12-36 h. Several studies have shown that copeptin values are increased in patients with AMI at admission, especially in early presenters (4,6,10,11,(17)(18)(19)(20)(21)(22)(23). We were able to illustrate for the first time that copeptin values were al- Thirty-five patients with AMI and SOT ≤180 min and 20 patients with AMI and SOT >180 min were included in this study.…”
Section: Discussionmentioning
confidence: 61%
“…The temporal release pattern of copeptin in our study was characterized by increased values very early after symptom onset, a peak in ambulance or at admission, and a rapid decrease within the first hours after admission. Copeptin concentrations returned to baseline in all diagnoses after 12-36 h. Several studies have shown that copeptin values are increased in patients with AMI at admission, especially in early presenters (4,6,10,11,(17)(18)(19)(20)(21)(22)(23). We were able to illustrate for the first time that copeptin values were al- Thirty-five patients with AMI and SOT ≤180 min and 20 patients with AMI and SOT >180 min were included in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Second, the ROC-derived cut-off values of hs-cTnT for AMI diagnosis were based on a high-risk population presenting with symptoms suggestive of AMI. The algorithm therefore requires confirmation and validation in a lower-risk cohort [24,25]. Third, we did not explore either a sex-specific cut-off value for the hs-cTnT assay, or the potential value Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/16/15 2:35 PM of dynamic change in hs-cTnT level as a diagnostic tool [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…This evidence might be used as a (rule-in) warning to ED physicians regarding patients who need urgent triage and a more aggressive treatment. In fact, according to the signifi cant increase of copeptin in the individuals displaying a marked stress reaction, the emergency setting seems to be the ideal environment to fully exploit the information carried by the measurement of this marker and assess the risk for an acute life-threatening condition (85,86,88,92,93) .…”
Section: Discussionmentioning
confidence: 99%